Studi Popularitas, Akseptabilitas, dan Elektabilitas Muhaimin Iskandar pada Pilpres 2024 di Kalangan Alumni Pesantren Mamba’ul Ma’arif Denanyar Jombang - Umma, Syafiatul; Holilah, Holilah (Jurnal Review Politik, 2023)
This research is motivated by the news of the progress of KH. Muhaimin Iskandar in the 2024 presidential election which received positive and negative comments among the public, including from alumni of the Mamba'ul Ma'arif Denanyar Islamic boarding school, Jombang. Santri alumni are considered to have different thoughts about the world of politics compared to when they were still students who were known for their obedience to the Kiai. Alumni have been influenced by various factors which ultimately shape new thinking about social and political issues. This study aims to determine how big the level of popularity, acceptability, and electability of KH. Muhaimin Iskandar in the 2024 presidential election among alumni of the Mamba'ul Ma'arif Islamic boarding school students, Denanyar, Jombang. This study uses the concept of popularity, acceptability, and electability theory. The type of research used in this research is descriptive quantitative research method. This study used a sample of 98 respondents which was carried out by random sampling technique. Data collection techniques are observation, questionnaires, and documentation. While the data analysis used percentage descriptive analysis with the SPSS application. The results of this study indicate the level of popularity of Muhaimin Iskandar in the 2024 presidential election among alumni of Mamba'ul Ma'arif Denanyar Islamic boarding school students by 84.7%, acceptability by 73.5% and electability by 65.3%. Total electability of KH. Muhaimin Iskandar is rated lower than the sum of his popularity and acceptability. This shows that there are alumni of Mamba'ul Ma'arif Denanyar Jombang Islamic boarding school students who only know or accept, not choose KH. Muhaimin Iskandar as president in 2024. Alumni of the Mamba'ul Ma'arif Islamic boarding school Denanyar Jombang are also multi-party, but the party with the highest electability is the National Awakening Party (PKB).